Simultaneous determination of ruminal niacin, pyridoxine, thiamin and riboflavin levels by high performance liquid chromatography - Chhabra, Aruna; Dudhe, Anuja (The Indian Journal of Animal Sciences, 2012)
A sensitive and specific ion-pair reversed phase high performance liquid chromatographic (HPLC) method for the separation and simultaneous determination of niacin, pyridoxine, thiamin and riboflavin in rumen liquor samples is described. The vitamins were extracted from rumen liquor using 0.2 NHâ‚‚S0â‚„ and diastase enzyme. The procedure enabled extraction of bound and unstable vitamins and provided clear extracts for analysis. HPLC was carried out on licrosper RP-18. All the 4 vitamins were satisfactorily separated in less than 10 min with a single injection using a tunable absorbance detector at 280 nm. Peak elution order was niacin, pyridoxine, thiamin and riboflavin. The amount of amine modifier in the mobile phase was critical to the separation of niacin and pyridoxine. The recoveries of niacin, pyridoxine, thiamin and riboflavin were in the ranges of 84.7-94.4%, 86.5-94.3%, 84.2-93.8% and 80.3-90.9%, respectively, and were detennined in the nanogram range as required in bio-viability studies.